Coordinating a Collegiate Service-Learning Mentoring Program - Emily Rickerson; Matthew Ohlson; Kate Fogarty; Muthusami Kumaran; Dale Pracht (EDIS)
Building a program like C.A.M.P. Gator for an institute of higher learning takes a great deal of planning, communication, and leadership. This 3-page fact sheet discusses the steps required to coordinate such a program. Written by Emily Rickerson, Matthew Ohlson, Kate Fogarty, Muthusami Kumaran, and Dale Pracht, and published by the UF Department of Family Youth and Community Sciences, August 2011. (Photo © C.A.M.P. Gator)